Gender analysis: Sub-Saharan African nurses' migration experiences - a systematic review - Mavodza, Constancia (Department of Public Health and Family Medicine, 2017)
Alleviating the global shortage of health workers, particularly nurses, is critical for health systems and health worker performance. Nurses are mostly women and make up the majority of the health workforce. Several factors have been identified as key players in the shortage crisis and migration is one of these factors. Nurses' migration from Sub Saharan Africa (SSA) increases the nurse shortage in the region and further constraints the already struggling health systems. Migration literature has dominantly focused on macro push-pull, brain drain and ethics theories of migration with limited exploration of relationships, interaction, norms, beliefs and values shaping migration trajectories and decisions. Despite the potential role of gender as an influential component of migration trajectories, there has been little research done to investigate gender in the context of migration of SSA nurses. This review aims to identify, describe, and summarize SSA nurses' migration experiences by assessing the influence of gender on these experiences. The dissertation is organized into 3 parts. Part A is a systematic review protocol that describes the background, justification and methodology of the review. A scoping exercise is conducted to to familiarize with the literature. This is followed by a qualitative systematic approach is utilised and the literature in eight databases is searched using key words and terms derived from an initial scoping exercise and the review questions. Suitable articles are defined and selected using a set inclusion and exclusion criteria. The suitable articles are then appraised and a thematic analysis using a gender focal lens is applied to them. Part B is a literature review of existing primary and theoretical research on health worker shortages; migration and gender analysis in health worker migration and shortages. It provides a background for the systematic review by defining migration, gender and gender analysis as well as presenting the scope on health worker and nurse shortages. The literature review encompasses the scoping exercise and concludes on the relevance of a gender-focused research on nurse migration. Part C. is the full systematic review presented as an article for Human Resources for Health Journal. Articles published on Sub-Saharan African (SSA) nurses' migration experiences between 2005 and 2016 are presented, subjected to a gender analysis to illuminate the results. The discussion and conclusion then follow. The results indicate that there is a paucity of empirical work on nurse migration experiences that is explicitly gender-focused. Gender analysis that is situated in social contexts and identifiers revealed that SSA nurses continuously renegotiate and reconfigure gender roles in child care as they move from one social context to another. Moreover migrating SSA nurse face challenges and limitations at macro, meso and micro levels of the system- that are linked to their identities as either professionals, African migrants and/or women. Therefore, the review underscores the importance of the relationships between gender and local/individual nuances and global/national determinants of migration. However, these studies are limited in their explicit gender and social focus and how it contextually affects health worker performance and quality care provision. More empirical studies are needed to investigate gender influences for migrating male nurses; nurses who remain; and by different geographical & cultural region – to allow comparison across different groups of nurses and determine conceptual generalizations for doing gender research. This dissertation will likely increase understanding of the role of gender in migration decision-making and experiences for SSA nurses across different professional, migrant and woman identities. This understanding has impacts on nurse motivation, capacity and capability as well quality care provision. Additionally, the dissertation provides a better understanding for incorporating gender analysis in health systems research, and also identifies avenues for future research.